Perbandingan randemen minyak atsiri sereh (cymbopogon citratus) yang umur panennya 6 bulan Dan 9 bulan dengan metode destilasi air) - Rani Prabandari (Viva Medika, 2017)
AbstractIndonesian nature is very rich in plants containing essential oils. Essential oils can be produced from various parts of plants such as roots, stems, leaves, flowers, or fruit. There are 50-200 species of essential oil producing plants. In Indonesia there are around 40 types of essential oils producing plants. One of the essential oils producing plants is lemongrass (Taufiq, Tuhana, 2008 p: 2). This study aims to determine the comparison of essential oils in Lemongrass (Cymbopogon citratus) which are harvested at 6 months and 9 months with a water distillation method. The procedure for selecting samples and research samples, directly with the object of research, is the citronella plant whose harvest age is 6 months taken from 1 clump and 9 months taken from 1 clump. The results of this study indicate that lemongrass plants with a harvest age of 6 months produce more essential oils compared to lemongrass plants with a harvest age of 9 months. This is influenced by several factors, including climate, harvest age. Lemongrass plants aged 6 months are the optimal age to be harvested, so that they get a higher yield of essential oils, besides that the factors of soil fertility and the intensity of sunlight also affect the content of essential oils of lemongrass.From the results of the research that has been done on the test sample, it can be concluded that the results of the essential oil ration on citronella (Cymbopogon citratus), which has 6 months of harvest age, obtained an average yield of 0.46% v / b and 9 months. 0.35% v / b with the results of the t-test obtained by the price t-count (2.984)> t-table (2.776). So that H0 is rejected and Ha is accepted and it can be concluded that there is a significant difference between lemongrass with 6 months and 9 months of harvest. Keywords: lemongrass, essential oil, age of harvest, water distillation